Human digital thought clones: the Holy Grail of artificial intelligence for big data - Truby, Jon; Brown, Rafael (Information & communications technology law, 2021)
This article explores the legal and ethical implications of big data's pursuit of human 'digital thought clones'. It identifies various types of digital clones that have been developed and demonstrates how the pursuit of more accurate personalised consumer data for micro-targeting leads to the evolution of digital thought clones. The article explains the business case for digital thought clones and how this is the commercial Holy Grail for profit-seeking big data and advertisers, who have commoditised predictions of digital behaviour data. Given big data's industrial-scale data mining and relentless commercialisation of all types of human data, this article identifies some types of protections but argues that more jurisdictions urgently need to enact legislation similar to the General Data Protection Regulation in Europe to protect people against unscrupulous and harmful uses of their data and the unauthorised development and use of digital thought clones.